Pengaruh Komitmen Organisasi, Budaya Organisasi, Karakteristik Individu Terhadap Organizational Citizenship Behavior - Rina Irawati; Budi Prasetyo, Irawan (Bulletin of Management and Business, 2021)
Organizational Citizenship Behavior is not well known, but basically employees in a company or organization have sometimes implemented OCB in their work. OCB is reflected in the behavior of helping others, volunteering for extra tasks, obeying the rules and procedures in the workplace. This behavior illustrates the added value of employees which is a form of prosocial behavior, namely positive, constructive and helpful social behavior. The research object is the employees of PT Jatidiri Primaraya in Pasuruan. The purpose of this study was to determine the effect of Organizational Commitment, Organizational Culture, and Individual Characteristics on Organizational Citizenship Behavior. The results prove that organizational commitment, organizational culture and individual characteristics partially influence OCB, where the organizational culture variable (X2) has a dominant influence with the largest beta value, namely 0.464. This research is supported by previous research, namely Fuad, Ahmad, et.al (2020), Novariani, Indri, et.al (2016), and Nasichudin, et.al (2016).